2003
DOI: 10.1128/aem.69.4.1973-1979.2003
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Malolactic Activity Is a Characteristic of H+-ATPase-Deficient Mutants of the Lactic Acid BacteriumOenococcus oeni

Abstract: The lack of malolactic activity in H ؉ -ATPase-deficient mutants of Oenococcus oeni selected previously was analyzed at the molecular level. Western blot experiments revealed a spot at 60 kDa corresponding to the malolactic enzyme only in the parental strain. Moreover, the mleA transcript encoding the malolactic enzyme was not detected by reverse transcription (RT)-PCR analysis of mutants. These results suggest that the malolactic operon was not transcribed in ATPase-deficient mutants. The mleR gene encoding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(31 reference statements)
3
10
0
Order By: Relevance
“…Similar to mutants in other studies (23,24,52), these mutants had slower growth at pH 4.5 (results not shown). In addition, the ATPase activities of mutant cells were lower than those of the parent strain, and the four mutant strains selected for further study had 52 to 62% less F 0 F 1 -ATPase activity than the parent strain, which corresponded to activities of 2.9 to 3.6 mol P i min Ϫ1 mg Ϫ1 (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Similar to mutants in other studies (23,24,52), these mutants had slower growth at pH 4.5 (results not shown). In addition, the ATPase activities of mutant cells were lower than those of the parent strain, and the four mutant strains selected for further study had 52 to 62% less F 0 F 1 -ATPase activity than the parent strain, which corresponded to activities of 2.9 to 3.6 mol P i min Ϫ1 mg Ϫ1 (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Due to the simplicity and lower time consumption of FCM associated with fluorescent probes, we simultaneously measured pH in and ΔΨ throughout MLF, both in synthetic medium and in wine, and determined their changes. Moreover, with the vitality descriptor ΔFI 15 , we confirmed ATP synthesis, as suggested by (Galland et al, 2003). The kinetics of physiologic cellular changes of O. oeni are illustrated in Fig.…”
Section: Cell Parameter Changes During Mlfsupporting
confidence: 77%
“…The role of ATPase in relation to acid tolerance has been demonstrated with ATPasedeficient mutants (Tourdot-Maréchal et al, 1999). Since all the ATPase-deficient mutants lack malolactic activity, a link has been suggested between ATPase and malolactic activity in O. oeni (Galland et al, 2003), and, moreover, it has been observed that ATPase activity was maximal in the exponential growth phase of O. oeni (Carrete et al, 2002). It has been demonstrated (Salema et al, 1996b) that MLF generates both a transmembrane pH gradient and an electrical potential gradient ΔΨ in O. oeni, and that the latter controls the rate of fermentation.…”
Section: Introductionmentioning
confidence: 97%
“…Radiolabeling with [ 35 S]methionine has been used to study protein profiles in this bacterium under stress conditions (14,15). Immunoblotting has been used to study the expression of specific proteins, e.g., malolactic enzyme (12,23), [H ϩ ]ATPase (43), and Lo18 (16,18,43).…”
mentioning
confidence: 99%